2013
DOI: 10.3390/rs5105006
|View full text |Cite
|
Sign up to set email alerts
|

Processing and Assessment of Spectrometric, Stereoscopic Imagery Collected Using a Lightweight UAV Spectral Camera for Precision Agriculture

Abstract: Imaging using lightweight, unmanned airborne vehicles (UAVs) is one of the most rapidly developing fields in remote sensing technology. The new, tunable, Fabry-Perot interferometer-based (FPI) spectral camera, which weighs less than 700 g, makes it possible to collect spectrometric image blocks with stereoscopic overlaps using light-weight UAV platforms. This new technology is highly relevant, because it opens up new possibilities for measuring and monitoring the environment, which is becoming increasingly imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
445
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
2
2
2

Relationship

2
4

Authors

Journals

citations
Cited by 443 publications
(451 citation statements)
references
References 40 publications
4
445
2
Order By: Relevance
“…The effect was the most noticeable in the 'Barley UAV 140 m' dataset, which was collected during 4.5 h, when illumination changed significantly, and in the 'Grass UAV 50 m' dataset, which was collected during sunny conditions at a low flying height that caused remarkable anisotropy effects ( Figure 5). Multiple studies have shown that radiometric correction using the RBA method improved the uniformity of image orthomosaics [7,11,12,63,77]. Our results showed that the corrections also improved the accuracy of the crop parameter estimations.…”
Section: Discussionsupporting
confidence: 64%
See 4 more Smart Citations
“…The effect was the most noticeable in the 'Barley UAV 140 m' dataset, which was collected during 4.5 h, when illumination changed significantly, and in the 'Grass UAV 50 m' dataset, which was collected during sunny conditions at a low flying height that caused remarkable anisotropy effects ( Figure 5). Multiple studies have shown that radiometric correction using the RBA method improved the uniformity of image orthomosaics [7,11,12,63,77]. Our results showed that the corrections also improved the accuracy of the crop parameter estimations.…”
Section: Discussionsupporting
confidence: 64%
“…where A priori values and standard deviations used in this study (Table 6) were selected based on suggestions by Honkavaara et al [7,63]. During the drone-based grass data collection, weather was mainly sunny (see Table 2); therefore, we used the BRDF correction to compensate for the reflectance anisotropy effects.…”
Section: Radiometric Processingmentioning
confidence: 99%
See 3 more Smart Citations